Decomposing the Labour Productivity Gap between Migrant-Owned and Native-Owned Firms in Sub-Saharan Africa. Issue 9 (2nd September 2019) - Islam, Asif; Palacios Lopez, Amparo; Amin, Mohammad
Abstract: Migration studies have been primarily based on the movement of individuals from developing to developed economies, with a focus on the impact of migrants on host country wages. In this study we take a different angle by exploring the labour productivity of migrant-owned firms versus native-owned firms in 20 African economies using firm-level data. We find that labour productivity is 78 per cent higher in migrant-owned firms than native-owned firms. Using the Oaxaca-Blinder decomposition method we find that structural effects account for 80 per cent of the labour productivity gap. Returns to manager education largely explain the productivity advantage of migrant-owned firms over native-owned firms. Interactions with the government, access to finance, informality, and power outages are also considerable contributors to the labour productivity gap.